Contraceptive intentions among Christian women in India: a multi-stage Logit model analysis - Joshi, Niyati; Singh, Mahesh Nath (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The main objective of this paper is to find how end level service providers of contraceptives can meet problems in identifying specific non-users at different stages of service delivery. Methods: A multi-stage Logit model is developed from NFHS (2005-06) data for Christian women in India. The initial model is selected by Brown screening technique and for the final model, likelihood ratio statistic and Akaike information criterion is used. The study variables are age, number of living children, unmet need, infecundity, side effects of contraceptive use, education and place of residence, SLI and cash earning. Results: Though spatial factors affect both Christian and non-Christian women, SLI directly affect Christian womens’ intention while it operates through education for non-Christian women. The best model for future contraceptive intention among Christian women is affected by unmet need operating through standard of living. Conclusions: The study finds two different paths of causation affecting future contraceptive intentions of Christian and non-Christian women with separate policy concerns and suggests that paths to future contraceptive intentions of Christian women may act as a social learning through diffusion process for non-Christian women.